2018
DOI: 10.1101/453068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing the Capping Efficiency of the Sindbis Virus nsP1 Protein Negatively Affects Viral Infection

Abstract: 25Alphaviruses are arthropod-borne RNA viruses that are capable of causing severe 26 disease and are a significant burden to public health. Alphaviral replication results in the 27 production of both capped and noncapped viral genomic RNAs, which are packaged 28 into virions during the infections of vertebrate and invertebrate cells. However, the roles 29 that the noncapped genomic RNAs (ncgRNAs) play during alphaviral infection have yet 30 to be exhaustively characterized. Here, the importance of the ncgRN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The alterations in ns and structural protein levels upon bortezomib treatment also reflect a similar phenotype recently described for a SINV mutant with increased nsP1 capping activity [55]. This mutant over-produced ns proteins and had somewhat elevated levels of viral RNA synthesis.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 78%
See 1 more Smart Citation
“…The alterations in ns and structural protein levels upon bortezomib treatment also reflect a similar phenotype recently described for a SINV mutant with increased nsP1 capping activity [55]. This mutant over-produced ns proteins and had somewhat elevated levels of viral RNA synthesis.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 78%
“…This mutant over-produced ns proteins and had somewhat elevated levels of viral RNA synthesis. Importantly, it also had slightly reduced synthesis of structural proteins and strongly reduced infectious virion production [55]. These similarities indicate that disrupting the balance between ns and structural protein levels is detrimental for alphavirus replication, perhaps by altering the cellular environment in a way that is unfavorable for virion formation and/or by directly interfering with virion formation.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 98%
“…Recently, it was reported that noncapped RNAs have an important relevance during SINV infection in an in vitro and in vivo model, since when the viral protein involved in cap addition (nsP1) was mutated to decrease the amount of cap on viral RNAs a slight decrease in mortality of infected mice was observed. Conversely, an increased addition of cap resulted in an almost complete abrogation of mortality and morbidity compared to mice infected with a wild type virus (34,35). Thus, in SINV noncapped RNAs play a critical role in determining whether the virus is neurovirulent or not, however if the cap structure has a role in genome encapsidation is not known.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that the virus population is maintained by constituents with a small number of mutations. In other words, progeny virus with a high number of mutations is not capable of replicating and this could be a reason for low specific infectivity (pfu/copy number of viral genome) in addition to other observations, such as the absence of RNA capping in the viral genome(LaPointe et al, 2018). The replication incompetence of the high-mutation-containing population might interfere with the replication-competent members by competing for viral receptors or inducing innate immune responses.…”
Section: Discussionmentioning
confidence: 99%